Sinar Harian, 3 April 2008 - [author not identified] (Selangor Karangkraf Sdn Bhd, 2008)
In June 1992, a total of 178 Heads Of State (including Malaysia) attending the Conference Peak Earth Nation-United in Rio De Janerio, Brazil